1998
DOI: 10.1200/jco.1998.16.11.3649
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II trial of the safety and efficacy of shark cartilage in the treatment of advanced cancer.

Abstract: Under the specific conditions of this study, SC as a single agent was inactive in patients with advanced-stage cancer and had no salutary effect on quality of life. The 16.7% rate of SD was similar to results in patients with advanced cancer treated with supportive care alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
43
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(44 citation statements)
references
References 23 publications
1
43
0
Order By: Relevance
“…When alternative therapies were used as first-line treatment in a group of 33 women with breast cancer, early death and higher rates of recurrence were reported [23]. Furthermore, when tested in rigorous clinical trials, all ''natural cancer cures'' examined so far, such as shark cartilage [24,25], either have shown no benefit or, in the case of others such as laetrile [26], were found to be both ineffective and toxic. Fortunately, even for patients with advanced disease, most (88%) receive CAM care concurrently with conventional treatment [27] and it is the minority (8% in one study) who choose solely alternative cancer care [28].…”
Section: Risks Of Alternative Cancer Carementioning
confidence: 99%
“…When alternative therapies were used as first-line treatment in a group of 33 women with breast cancer, early death and higher rates of recurrence were reported [23]. Furthermore, when tested in rigorous clinical trials, all ''natural cancer cures'' examined so far, such as shark cartilage [24,25], either have shown no benefit or, in the case of others such as laetrile [26], were found to be both ineffective and toxic. Fortunately, even for patients with advanced disease, most (88%) receive CAM care concurrently with conventional treatment [27] and it is the minority (8% in one study) who choose solely alternative cancer care [28].…”
Section: Risks Of Alternative Cancer Carementioning
confidence: 99%
“…In advanced cancer, there is growing evidence that some patients have unrealistic expectations of treatments of minimal (Slevin et al, 1990) or unproven efficacy (Bagenal et al, 1990;Daugherty et al, 1995;Miller et al, 1998), including a belief that their cancer is curable (Slevin et al, 1990;Yates et al, 1993;Butow et al, 1999;Richardson et al, 2000). In a secondary analysis of data that evaluated the beliefs and attitudes of patients about their diagnosis, prognosis, satisfaction with and use of treatments in advanced cancer, we showed that positive illusory responses, characterised by a belief in curability, a strong will to live and a committed use of alternatives to conventional medical treatments were associated with better quality of life (Beadle et al, 2004).…”
mentioning
confidence: 99%
“…30) Also, in some cases, the final sample size was very small with no significant results. Furthermore, except for the trial conducted by Miller et al, 29) the results obtained in these clinical studies have not been published in peer-reviewed journals. These facts have led to inconclusive and unreliable results.…”
mentioning
confidence: 99%
“…29) In spite of these discouraging results, the use of complementary medications, including shark cartilage, have increased among cancer patients as shown in a survey performed among 143 advanced cancer patients in which the authors found that shark cartilage was used by 21 (10.7%) of those patients. 32) However, there has outspoken criticism of the shark cartilage use in cancer patients in light of the lack of sufficient clinical evidence.…”
mentioning
confidence: 99%
See 1 more Smart Citation